Antibacterial Properties of Canine Platelet-Rich Plasma and Other Non-Transfusional Hemo-Components: An in vitro Study - Attili, Anna-Rita; Iacoucci, Cristina; Serri, Evelina; Cuteri, Vincenzo; Cantalamessa, Andrea; Linardi, Martina; Rifici, Claudia; Mazzullo, Giuseppe; Rossi, Giacomo; Galosi, Livio; Tambella, Adolfo Maria (Frontiers in Veterinary Science, 2021)
This in vitro study was carried out to evaluate the potential antibacterial properties of canine non-transfusional hemo-components. Therapeutic formulations commonly used for regenerative medicine purposes (platelet-rich plasma, platelet gel, platelet lysate, fibrin glue), considering both leukocyte-rich and leukocyte-poor formulations, but also platelet-poor plasma and activating substances (thrombin, calcium gluconate), were tested to detect elements with potential antimicrobial properties. The antibacterial effect was tested on different bacterial strains (Staphylococcus aureus subspecies aureus, Staphylococcus cohnii subspecies cohnii, Escherichia coli, Pseudomonas aeruginosa, and Klebsiella pneumoniae subspecies pneumoniae) isolated from canine wounds and classified as susceptible, multidrug-, extensively, and pandrug-resistant bacteria toward a known panel of human and veterinary antibiotics. The evaluation was carried out by agar gel diffusion method (Kirby–Bauer) and micro-inhibition in broth using microplates and spectrophotometer reading. The study findings confirmed the hypothesized antibacterial properties of canine non-transfusional hemo-components. A more effective bacteriostatic effect was found against Gram-negative bacteria, drug-resistant too. The presence of leukocytes or platelets does not appear to be essential for the antibacterial effect. Further studies should be conducted to evaluate the exact mechanism of action of the antimicrobial activity. However, non-transfusional hemo-components could be a useful natural aid in controlling bacterial infections in dogs.